2012
DOI: 10.3329/jsr.v5i1.11935
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Properties of the Newly Developed LiF:Mg,Cu,Si TL Material

Abstract: The dosimetric properties of the newly developed thermoluminescence (TL) material (LiF:Mg,Cu,Si) at Korea Atomic Energy Research Institute (KAERI) were investigated. The energy response of the detector was performed for photon energies from 20 to 662 keV. The dose response for this TL material (LiF:Mg,Cu,Si) was linear up to 10 Gy and a sublinear response was observed for higher doses. The reusability of this newly developed TL detector sufficiently satisfied IEC standards. Detection threshold of LiF:Mg,Cu,Si … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…The minimum measurable dose value of 0.3 µGy as 3σ of the background readout of unirradiated samples was reported [25]. The reusability of this newly developed TL detector sufficiently satisfied IEC standards [80]. It is also reported [81] that indigenously developed 6 LiF:Mg,Cu,Si and 7 LiF:Mg,Cu,Si TLDs provided a better alternative to TLD-600 and TLD-700 for the dosimetry of mixed fields of neutrons and gamma rays.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…The minimum measurable dose value of 0.3 µGy as 3σ of the background readout of unirradiated samples was reported [25]. The reusability of this newly developed TL detector sufficiently satisfied IEC standards [80]. It is also reported [81] that indigenously developed 6 LiF:Mg,Cu,Si and 7 LiF:Mg,Cu,Si TLDs provided a better alternative to TLD-600 and TLD-700 for the dosimetry of mixed fields of neutrons and gamma rays.…”
mentioning
confidence: 77%
“…Therefore, the authors strongly believed that LiF:Mg,Cu,P could be replaced by LiF:Mg,Cu,Si in the field of radiation dosimetry. Lee et al [77] and Kim et al [80] reported that for the reader annealing using a maximum readout temperature and clamping at 260 0 C, no significant change in the TL sensitivity and glow curve structure was observed for more than 100 reuse cycles of exposures (5.5 mGy) and readout. However, requirement of dual-step annealing method, for restoration of sensitivities of peaks 1-4, is indicative of complex nature of defects in this triplydoped phosphor.…”
mentioning
confidence: 99%
See 1 more Smart Citation